Controle das estruturas cristalinas e Anisotropias Magnéticas em filmes à base de Co e Gd - Bertelli, Tiago Pulce (2015)
In this work, we present a systematic investigation of the experimental parameters [inclination angle between the normal of the substrate plane and deposition flux direction a; angular velocity of the sample holder ?; magnetic field application during deposition HD; substrate temperature TS] on the values of the cubic HKC, uniaxial HKU and exchange bias HEB anisotropy of Co and Gd thin films, bilayers of Co/IrMn and IrMn/Gd and trilayers of Co/IrMn/Gd prepared by DC Magnetron Sputtering. Using the X-ray diffraction technique, it is demonstrated that, regardless the values of a, ? and HD parameters, Co films were deposited on the Ta seed layer oriented in the [111] direction with face centered cubic (fcc) structure. For the Gd films grown on the Ta seed layer, it was shown that as higher is the TS value, larger is the internal stress in Gd films; a feature that favors stabilization of the fcc-type phase for Gd thickness tGd of 10 nm. The increase of tGd or decrease of TS value causes structural relaxation to the hexagonal close packed hcp phase; it occurs on top of fcc-type Gd structure grown on Ta seed layer. Concerning the anisotropy fields (measured by ferromagnetic resonance technique FMR), it is demonstrated that due to the oblique deposition a ? 0°, one can control the HKU field of Co film. Specifically, for the Co film prepared at a = 55°, ? = 0 rpm and HD nulo, a maximum value of HKU = 72 Oe was obtained. It was possible to project samples with pure cubic or uniaxial and combined HKC + HKU fields by using oblique deposition for low a values (22 = a = 40°) with different rotation speeds ? (0, 30 and 40 rpm) of the sample holder during Co depositions. It was found that the HKC field remains approximately constant (? 2.8 Oe) regardless of a, ? and HD values, while the HKU field linearly decreases with the increasing of the angular velocity ? at a rate of 0.35 Oe/rpm (sample-holder central position: 15.7 = HKU = 1.4 Oe and sample-holder edge positions: 20.6 = HKU = 6.5 Oe for the range 0 = ? = 40 rpm, respectively). Using magnetometry measurements, it is shown that the fcc phase of Gd presents magnetization of 175 emu/cm3 and coercive field of 100 Oe, nearly constants in a wide temperature range (10 = T = 400 K), while the hcp Gd phase shows large coercive fields (HC = 480 Oe) and saturatation magnetization (MS = 640 emu/cm3 ) at 60 K, before spin reorientation phenomenon. Comparing Co/IrMn bylayers prepared with HD = 0 and HD ? 0 (applied to the film plane), it wasfound a significant increase of both uniaxial HKU (13 ? 33 Oe), and exchange bias HEB (33 ? 55 Oe) fields for samples located at the sample-holder central position. In addition, for bilayers samples fabricated at the sample-holder edge positions, the rotation of the xii sample enhances much more the HKU value (130%); an effect associated with the variation of a angle during the sample rotation. For Co/IrMn/Gd trilayers prepared at the sample-holder edges, the HKU field presents an anomalous increase (~ 45 ? ~ 220 Oe, 5 times bigger), accompanied by an increase of 45% in the HEB field related to the Co/IrMn interface (~ 55 ? ~ 80 Oe). This behavior may be due to the presence of ferromagnetic Gd deposited on top of texturized [111] IrMn layer. In fact, it diserves additional investigations since its physical origin is not yet understood.